Deletion of Tuberous Sclerosis 1 in Somatic Cells of the Murine Reproductive Tract Causes Female Infertility - Tanaka, Yoshihiro (Endocrine Society, 2012)
Tumors develop with dysregulated activation of mammalian target of rapamycin (mTOR), the kinase activity of which is kept in an inactive state by a tumor suppressor dimer containing tuberous sclerosis 1 (TSC1) and TSC2. We examined whether conditional deletion of TSC1 by a knock-in allele of the anti-Müllerian hormone type 2 receptor (Amhr2) driving Cre expression and subsequent activation of mTOR in granulosa cells and in oviductal and uterine stromal cells affects fertility in female mice. Increased phosphorylation of ribosomal protein S6, a downstream target of activated mTOR, was observed in all AMHR2-expressing tissues examined, indicating loss of TSC1 activity. TSC1 deletion in granulosa cells led to the detection of significantly fewer primordial follicles in mutant mice at 12 wk, suggesting premature ovarian insufficiency, which might be related to the significantly increased time mutant mice spent in estrus. Although the number of good-quality ovulated oocytes was not significantly different compared with controls, there was a significantly higher number of degenerated oocytes after normal and superovulation, suggesting compromised oocyte quality, as well. Natural mating also showed severalfold higher numbers of degenerate bodies in the mutants that collected in bilateral swellings resembling hydrosalpinges that formed in all mice examined because of occlusion of the proximal oviduct. Attempts to transfer control embryos into mutant uteri also failed, indicating that implantation was compromised. Endometrial epithelial cells continued to proliferate, and quantitative RT-PCR showed that mucin 1 expression persisted during the window of implantation in mutant uteri, without any changes in progesterone receptor mRNA expression, suggesting a mechanism that does not involve disrupted estradiol-regulated progesterone receptor expression. Homozygous deletion of TSC1 in reproductive tract somatic tissues of mice rendered females completely infertile, which is likely due to these pleiotropic effects on follicle recruitment, oviductal development, and blastocyst implantation.